Fano resonances and slow light in a nanocavity assisted by metallic nanoparticles‐quantum dot system. Issue 7 (23rd December 2022) - Chen, Chen; Wang, Yaxue; Wang, Wenjuan; Wang, Shengjia; Xiahou, Kuan; Yu, Chunchao; Xiao, Xun; Chen, Fang; Zhang, Huafeng; Sun, Lihui
Abstract: Double Fano resonances in a nanocavity assisted by metallic nanoparticles (MNPs)‐quantum dot (QD) system are demonstrated theoretically. The nanocavity is assumed to couple with the QD and QD is assumed to locate in the plasmon field produced by two excited MNPs nearby. The nanocavity is driven by a control field and a probing field. Double Fano resonances can be manipulated by the system parameters such as frequency detuning and coupling strength among the nanocavity, the mechanical oscillator, MNPs and QD. Especially, we find the second Fano resonance appears due to the interaction between the nanocavity with the QD‐MNPs. We also discuss the transmission and group delay in the double Fano resonance transparency windows which show tunable fast and slow light for different probe frequency. Our results may provide possible applications in designing optical buffer, switching, and so forth. Abstract : Double Fano resonances in a nanocavity assisted by metallic nanoparticles(MNPs)‐quatnm dot(QD) system are demonstrated theoretically. And it can manipulated by the system parameters such as frequency detuning and coupling strength among the nanocavity, the mechanical oscillator, MNPs and QD. The system shows tunable absorption, transmission and fast‐and‐slow light for different probe frequency.